2022
DOI: 10.4103/njcp.njcp_466_20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Psychosocial Determinants of Patients with Tuberculosis/Human Immunodeficiency Virus Co-Infection

Abstract: Background: Tuberculosis (TB)/human immunodeficiency virus (HIV) co-infection is a complex mesh of physical and psychosocial disorders that require a multimodal and multifaceted approach for improved outcomes. Aims: This study determined the treatment outcomes of patients with TB/HIV co-infection and the clinico-psychosocial predictors of the disease over a 10-year period in resource-limited settings. Patients and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Two studies conducted in Ethiopia found HIV status linked to increased odds of reporting perceived stigma among patients with TB [ 26 , 46 ]. Additional studies indicate similar findings [ 47 ] as well as a relationship between HIV status and overall stigma in patients with TB[ 48 ]. Syndemic stigma is likely underlying what we observed in our study, where two simultaneously occurring HIV and TB epidemics with their related stigmas are intertwined [ 37 ].…”
Section: Discussionsupporting
confidence: 55%
“…Two studies conducted in Ethiopia found HIV status linked to increased odds of reporting perceived stigma among patients with TB [ 26 , 46 ]. Additional studies indicate similar findings [ 47 ] as well as a relationship between HIV status and overall stigma in patients with TB[ 48 ]. Syndemic stigma is likely underlying what we observed in our study, where two simultaneously occurring HIV and TB epidemics with their related stigmas are intertwined [ 37 ].…”
Section: Discussionsupporting
confidence: 55%
“…Delays in establishing the diagnosis of TB in the absence of bacteriological support and other supportive investigations could partly explain the high mortality in this study. Other important factors that contribute to death among HIV patients but not addressed by this study include lack of adherence to ART and TB treatment as well as the duration of symptoms prior to presentation [44][45][46].…”
Section: Discussionmentioning
confidence: 97%
“…[2,9] Undernutrition, diabetes, smoking, harmful alcohol consumption, poor treatment adherence to anti-TB drugs; previous haphazard or poor implementation of isoniazid prophylaxis and previous ineffective TB treatment, especially in private practice; increasing treatment failure and loss to follow-up, poor Xpert MTB/RIF diagnostic coverage; and a high burden of human immunodeficiency virus (HIV) coinfection in low-resource settings, including Nigeria, are potential drivers for the high prevalence of resistant TB. [13][14][15][16][17][18][19][20][21][22] Higher prevalence of social determinants such as poverty, inequality, unsafe housing, discrimination, and social stigma in low-resource settings such as Nigeria also plays a significant role in the spread of DR-TB. [13,14,20] According to the 2019 WHO global TB report, Nigeria has one of the highest burdens of MDR/RR-TB, accounting for 4.2% of new cases and 15% of previously treated MTB.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22] Higher prevalence of social determinants such as poverty, inequality, unsafe housing, discrimination, and social stigma in low-resource settings such as Nigeria also plays a significant role in the spread of DR-TB. [13,14,20] According to the 2019 WHO global TB report, Nigeria has one of the highest burdens of MDR/RR-TB, accounting for 4.2% of new cases and 15% of previously treated MTB. [2] The reported figure is comparable to those from South Africa, but higher than the regional average and lower than Somalia's notification rate of 8.7% from new cases.…”
mentioning
confidence: 99%